Scholl reaction as a powerful tool for the synthesis of nanographenes: a systematic review. Issue 51 (29th September 2021) - Jassas, Rabab S.; Mughal, Ehsan Ullah; Sadiq, Amina; Alsantali, Reem I.; Al-Rooqi, Munirah M.; Naeem, Nafeesa; Moussa, Ziad; Ahmed, Saleh A.
Abstract : Nanographenes have been attracting increasing attention owing to their widespread applications in organic electronics. Polycyclic aromatic hydrocarbons are popular research subjects due to their high stability, planar structure and optical spectra. Abstract : Nanographenes, or extended polycyclic aromatic hydrocarbons, have been attracting increasing attention owing to their widespread applications in organic electronics. However, the atomically precise fabrication of nanographenes has thus far been achieved only through synthetic organic chemistry. Polycyclic aromatic hydrocarbons (PAHs) are popular research subjects due to their high stability, rigid planar structure, and characteristic optical spectra. The recent discovery of graphene, which can be regarded as giant PAH, has further stimulated research interest in this area. Chemists working with nanographene and heterocyclic analogs thereof have chosen it as their preferred tool for the assembly of large and complex architectures. The Scholl reaction has maintained significant relevance in contemporary organic synthesis with many advances in recent years and now ranks among the most useful C–C bond-forming processes for the generation of the π-conjugated frameworks of nanographene or their heterocyclic analogs. A broad range of oxidants and Lewis acids have found use in Scholl-type processes, including Cu(OTf)2 /AlCl3, FeCl3, MoCl5, PIFA/BF3 –Et2 O, and DDQ, in combination with Brønsted or Lewis acids, and the surface-mediated reaction has found especially wide applications in PAH synthesis. Undoubtedly, the utility of the Scholl reaction is supreme in the construction of nanographene and their heterocyclic analogues. The detailed analysis of the progress achieved in this field reveals that many groups have contributed by pushing the boundary of structural possibilities, expanding into surface-assisted cyclodehydrogenation and developing new reagents. In this review, we highlight and discuss the recent modifications in the Scholl reaction for nanographene synthesis using numerous oxidant systems. In addition, the merits or demerits of each oxidative reagent is described herein.